Total Factor Productivity Growth (TFPG) dan Determinan Produksi Tebu Indonesia - Diarty, Milie; Haryanto, Jasmine ‘Abqoriyah; Izzuddin, Kautsar Hilmi; Manganti, Marella Dea; Rahman, Muhamad Reza; Budiasih, Budiasih (Politeknik Statistika STIS, 2023)
The increase in Indonesia's sugar imports was due to production originating from within the country but unable to meet various needs for the domestic region. This shortage of sugar production is of course in line with the production of sugar cane which is the main ingredient and there are eight sugarcane producing centers in the province. Sugarcane production is closely related to the influence of production factors and production technology (TFP). This study aims to analyze the various influences on sugarcane production from land area and labor in eight sugarcane-producing provinces and to analyze the determinants of TFP growth (TFPG) using panel data regression. Where the results were obtained showing that the sugarcane planting area had a significant positive effect and labor had a negative but not significant effect. Foreign investment in agriculture and plantations and Farmers' Exchange Rates of plantation crops have a negative but not significant effect on the TFPG.